PENGARUH BIG FIVE PERSONALITY, KEPUASAN KERJA TERHADAP PRESTASI KERJA PEGAWAI KESYAHBANDARAN DAN OTORITAS PELABUHAN (KSOP) KELAS II KOTABARU-BATULICIN KABUPATEN TANAH BUMBU - Taufan Eka Putra; Arifin; Arfa, Aryatih (FEB Universitas Sam Ratulangi Manado, 2024)
This study aims to analyze the influence of big five personalities, job satisfaction on the work performance of Class I Kesyahbandaran and Port Authority (KSOP) employees of Kota Baru-Batulicin, Tanah Bumbu Regency. The data collection technique used is using questionnaires. For the population used, it is 81 employees. The data analysis method used in this study used SmartLPS software. SmartPLS is a component- or variance-based structural equation (SEM) model that is not based on many assumptions. The results showed that the big five personalities have a positive and significant influence on job performance, job satisfaction has a positive and significant effect on job performance.